2007
DOI: 10.1634/theoncologist.12-4-478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Total Costs of Chemotherapy-Induced Febrile Neutropenia: Results from a Pilot Study with Community Oncology Cancer Patients

Abstract: LEARNING OBJECTIVESAfter completing this course, the reader will be able to:1. Discuss the definitions of direct and indirect costs of medical care.2. Describe the feasibility of obtaining information on direct and indirect medical costs associated with febrile neutropenia.3. Identify clinical and nonclinical factors that are associated with larger estimates of direct and indirect medical costs for febrile neutropenia.Access and take the CME test online and receive 1 AMA PRA Category 1 Credit ™ at CME.TheOncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 17 publications
4
44
0
1
Order By: Relevance
“…15 In a pilot study involving patients with cancer from a community oncology center, total direct cost for inpatients being treated for lymphoma averaged €12,325 ($17,869) per patient, compared with a total cost of €7,142 ($10,354) for patients with breast cancer. 16 On the other hand, direct costs for outpatients were remarkably lower (lymphoma, €3,934 [$5,704]; breast cancer, €755 [$1,094]), similar to our findings, which illustrate how direct costs for treatment are lower for outpatients than for inpatients. Interestingly, the overall cost of a TIUH is not related to the patient's origin on a per-patient basis.…”
Section: Discussionsupporting
confidence: 89%
“…15 In a pilot study involving patients with cancer from a community oncology center, total direct cost for inpatients being treated for lymphoma averaged €12,325 ($17,869) per patient, compared with a total cost of €7,142 ($10,354) for patients with breast cancer. 16 On the other hand, direct costs for outpatients were remarkably lower (lymphoma, €3,934 [$5,704]; breast cancer, €755 [$1,094]), similar to our findings, which illustrate how direct costs for treatment are lower for outpatients than for inpatients. Interestingly, the overall cost of a TIUH is not related to the patient's origin on a per-patient basis.…”
Section: Discussionsupporting
confidence: 89%
“…147 [12] ( 128 [14] (98-158) results from purely theoretical approaches like the recently published papers on the cost-effectiveness of pegfilgrastim versus filgrastim before reaching definite conclusions [31][32][33]. Similarly, asymmetric distribution of cost has been shown for FN [7], CT-induced thrombocytopenia and bleeding [16].…”
Section: Health Economic Impact Clinical Implications and Further Rementioning
confidence: 99%
“…The existing health economic literature, mainly studies from the United States, focuses on particular toxic effects such as anaemia [11,13], febrile neutropenia (FN) [7,14,15], thrombocytopenia and bleeding [16,17], mucositis [18] and CT-induced nausea and vomiting [2]. However, information on the cumulative cost of toxicity management, e.g.…”
mentioning
confidence: 99%
“…Several studies, including a recent systematic review, have evaluated the economic burden associated with chemotherapy-related hematologic toxicity in the US [25,26,27]. These studies, taken together, demonstrated that these adverse events had a substantial economic impact on patients, payers, caregivers, and society in general [25].…”
Section: Discussionmentioning
confidence: 99%